Winter School on sEMG Signal Processing: An Initiative to Reduce Educational Gaps and to Promote the Engagement of Physiotherapists and Movement Scientists With Science - De la Fuente, Carlos; Machado, Álvaro S.; Kunzler, Marcos R.; Carpes, Felipe P. (Frontiers in Neurology, 2020)
The application of surface electromyography (sEMG) in neurology is sometimes limited by the scientific background regarding the use of sEMG. The students frequently will use sEMG only when developing graduate studies. To reduce these barriers we promoted a free Winter School on sEMG to Latin American students. The school was a 3-days event with theoretical classes and computer programming in Matlab. Lectures were delivered in Portuguese and Spanish to 50 participants. All lectures were recorded and made available on YouTube®. After the School, participants completed a written exam to receive a certificate. The written exam revealed the average effectiveness of 71±20% in the comprehension of topics addressed in the school. Participants rated the School as ‘excellent’ and considered that the event changed their thoughts about the use of sEMG. Limited mathematical skills or background were the main barriers identified to follow the lectures and make use of sEMG. We conclude that the Winter School had a positive impact on participant’s formation, especially by showing them the importance of continuous involvement with the concepts related to sEMG to become proficient in its use. From the participant’s point of view, the activity was excellent and the follow up of the school in YouTube® suggests that combining face-to-face activities followed by the online availability of lectures is a valid strategy to reinforce the learning process and reduce barriers in the use of sEMG. If similar results would happen for a paid registration event in an economically developing region still need investigation.